Engineering Software Systems: Research and Praxis - Kosiuczenko, Piotr; Zieliński, Zbigniew (Advances in Intelligent Systems and Computing, 2019)
This book highlights a range of new approaches and concepts in the field of software engineering. Based on systematic methods, graphical and formal models, the approaches are designed for solving practical problems encountered in actual software development. The book is divided into 13 chapters, which address core aspects such as security, performance and quality measurement. Chiefly intended to stimulate new research by presenting real problems faced by the industry, and to facilitate software development by applying precisely defined, validated and efficient models and methods, the book offers a valuable guide - for researchers and industry practitioners at small, medium and large companies alike. .